COMPARATIVE EVALUATION OF PHOTODYNAMIC THERAPY IN PURULENT INFLAMMATORY DISEASES OF THE MAXILLOFACIAL REGION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article presents a comparative evaluation of the effectiveness of photodynamic therapy (PDT) versus conventional treatment methods in purulent-inflammatory diseases of the maxillofacial region. The study involved 30 patients divided into two groups: those receiving conventional treatment and those treated with adjunctive photodynamic therapy. The results demonstrated that PDT rapidly and effectively eliminates microbial flora, significantly reduces inflammatory symptoms in a shorter period, and accelerates wound healing. Furthermore, the method proved effective against antibiotic-resistant microorganisms. Photodynamic therapy was assessed as a safe, modern, and promising treatment modality.
Keywords: Photodynamic therapy, maxillofacial region, purulent-inflammatory diseases, phlegmon, laser therapy, microflora, antibiotic resistance, surgical treatment, dentistry